The Impact of Visual Perturbation Neuromuscular Training on Landing Mechanics and Neural Activity: A Pilot Study - Timothy R Wohl; Cody R Criss; Adam L Haggerty; Justin L Rush; Janet E Simon; Dustin R Grooms (International Journal of Sports Physical Therapy, 2024)
# Background